The Influence of Product Quality Perception and Price Perception on the Purchase Decision of Sosro Bottled Tea in Surabaya - M. Yasser Abed; Hery Pudjoprastyono (International Journal of Economics (IJEC), 2023)
Based on Top Brand Index data, there has been a decline in sales of Teh Botol Sosro since 2018. This indicates a decrease in purchasing decisions. The purpose of this study is to determine the influence of product quality perception and price perception on the purchase decision of Sosro Bottled Tea in Surabaya. The method in this study uses quantitative methods. The data collection technique in this study used purposive sampling. The population in this study is consumers of Sosro Bottled Tea in Surabaya. The sample in this study amounted to 100 respondents. The data analysis technique used in this study used multiple linear regression method. The results of this study are 1. Based on the results of calculations and data analysis, it is known that Product Quality Perception has a significant positive effect on the purchase decision of Teh Botol Sosro in Surabaya, which means that if the Perception of Product Quality of Teh Botol Sosro increases it will be in line with consumer purchasing decisions. 2. Based on the results of calculations and data analysis, it is known that Price Perception has a significant positive effect on the purchase decision of Sosro Bottled Tea in Surabaya, which means that Price Perception is in line with consumer purchasing decisions